Instant StyleCop code analysis how-to : learn how to analyze and maintain code for your projects using StyleCop - Leveque, Franck (Packt Publishing, 2013)
Filled with practical, step-by-step instructions and clear explanations for the most important and useful tasks. The book will take a how-to approach, focusing on recipes that demonstrate Stylecop code analysis. Stylecop Code Analysis How-to is intended for developers and project managers who are looking for an all-encompassing overview of Stylecop to display or enforce their specific coding conventions. It is assumed that you have a minimal understanding of integration technologies such as MSBuild and Nant. You should also have some knowledge on how to program in C♯ and LINQ. An available versi.